Evaluation of Laser Fluorescence in the Monitoring of the Initial Stage of the De-/Remineralization Process: An in vitro and in situ Study - Spiguel, M. H.; Tovo, M. F.; Kramer, P. F.; Franco, K. S. [UNESP]; Alves, K. M. R. P. [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP] (Karger, 2009)
This study aimed to evaluate laser fluorescence (LF) for monitoring the initial stage of subsurface de- and remineralization (<150 mu m depth). Ninety-six sound blocks of bovine enamel, selected according to surface hardness (SH) and LF were used in two experimental studies, in vitro and in situ. In vitro, blocks were exposed to a demineralizing solution, then remineralized by pH cycling for 6 days. In situ, 10 volunteers wore acrylic palatal appliances, each containing 4 dental enamel blocks that were demineralized for 14 days by exposure to 20% sucrose solution. Following this treatment, blocks were submitted to remineralization for 1 week with fluoride dentifrice (1,100 mu g F/g). In both experiments, SH and LH were measured after demineralization and after remineralization. Further, enamel blocks were selected after the demineralization/remineralization steps for measurement of cross-sectional hardness and integrated loss of subsurface hardness (Delta KHN). SH and Delta KHN showed significant differences among the phases in each study. LF values for sound, demineralized and remineralized enamel were: 5.2 +/- 1.1, 8.1 +/- 1.2 and 5.6 +/- 0.8, respectively, in the in vitro study, and 5.3 +/- 0.3, 16.5 +/- 4.7 and 6.5 +/- 2.5, respectively, in the in situ study, values for demineralized enamel being significantly higher than for sound and remineralized enamel in both studies. However, LF was correlated with Delta KHN only in situ. LF was capable of monitoring de- and remineralization in early lesions in situ, when bacteria are presumably present in the caries lesion body, but is not correlated with mineral changes in bacteria-free systems. Copyright (C) 2009 S. Karger AG, Basel
Keywords: Demineralization; Dental caries; Laser fluorescence; Remineralization